Manajemen Keuangan Sekolah: Tinjauan Terhadap Pengelolaan Dana Bantuan Operasional Sekolah (BOS) - Muhsin, Ali; Mulyanti, Dety (Maisyatuna, 2023)
One aspect that is very important in the management of educational institutions (schools) is the financial aspect. School financial management must be carried out properly starting from planning, implementing, monitoring, evaluating, and reporting. This article discusses school financial management, in this case, the management of school operational assistance funds. These funds are a source of school funds that need to be managed transparently, accountably, effectively, and efficiently.